Organizational Sabotage: Antecedents, Independent Factors, and Their Implications for Performance Effectiveness - Desvi Emty (Suria Academic Press, 2026)
This study aims to explore the meaning of organizational sabotage within public service bureaucracy, focusing on its antecedent factors, cultural mediators, and implications for performance effectiveness in Kampar Regency, Riau, Indonesia. Employing a qualitative intrinsic case study design oriented toward Interpretative Phenomenological Analysis (IPA), data were collected through in-depth semi-structured interviews with 22 employees from three organizational units: the Investment and One-Stop Integrated Service Agency (DPMPTSP) of Kampar Regency, a telecommunications company, and a private hospital operating within Kampar Regency. Data collection was complemented by 12 weeks of participant observation and organizational document analysis. Reflexive thematic analysis identified four major themes: sabotage as a “silent language” manifested through administrative exclusion and knowledge concealment; relational justice wounds and supervisor ostracism as primary triggers; ewuh-pakewuh norms and the quality of Leader–Member Exchange (LMX) as cultural mediating and moderating mechanisms; and the erosion of service timeliness, team trust, and investment reputation as cumulative yet largely hidden consequences. The findings extend the understanding of sabotage from an individual deviation to a culturally structured meaning-making practice, leading to the development of the concept of “polite sabotage” as a localized form of counterproductive work behavior. This concept integrates Social Exchange Theory, Affective Events Theory, and the Job Demands–Resources Model within a hierarchical collectivist context. The study highlights the importance of interactional justice, strengthening leader–member exchange quality, and culturally grounded emotional regulation training. Future research is recommended to employ longitudinal designs and cross-cultural comparisons to psychometrically validate the construct of polite sabotage.